Puerarin induces platinum-resistant epithelial ovarian cancer cell apoptosis by targeting SIRT1. Issue 9 (September 2021) - Duan, Jianxiu; Yin, Mingyuan; Shao, Yaqin; Zheng, Jiao; Nie, Shengdan
Objective: Previous investigations indicated the anticancer activity of puerarin. The current study aimed to evaluate the effect and molecular mechanisms of puerarin in chemotherapy-resistant ovarian cancer cells. Methods: We examined the effects of puerarin in platinum-resistant epithelial ovarian cancer cells in vitro and in vivo . We also analyzed the molecular mechanism underlying Wnt/β-catenin inhibition and sirtuin 1 (SIRT1) regulation following puerarin treatment. Results: Our study demonstrated that puerarin effectively inhibited cell growth in vitro and in vivo by increasing apoptosis in ovarian cancer cells. More importantly, puerarin sensitized cisplatin-resistant ovarian cancer cells to chemotherapy. Puerarin treatment decreased SIRT1 expression, which attenuated the nuclear accumulation of β-catenin to inhibit Wnt/β-catenin signaling. In addition, SIRT1 overexpression diminished the effects of puerarin treatment on cisplatin-resistant ovarian cancer cells. Further analysis supported SIRT1/β-catenin expression as a candidate biomarker for the disease progression of epithelial ovarian cancer. Conclusions: Puerarin increased the apoptosis of platinum-resistant ovarian cancer cells. The mechanism is partly related to the downregulation of SIRT1 and subsequent inhibition of Wnt/β-catenin signaling.